Czech contribution to AHEAD2020: novel/alternative X-ray optics - René Hudec; Veronika Maršíková; Adolf Inneman; Peter Oberta; Ladislav Pína (Acta Polytechnica, 2025)
We briefly present selected results in the field of X-ray optics obtained within the project at the CTU in Prague in collaboration with other Czech Institutes, mainly Rigaku Prague, where X-ray optics modules were assembled. These efforts covered the simulations and designs of LE (Lobster Eye) and KB (Kirkpatrick-Baez) optical Systems, a study of new and alternative simulation/ray tracing methods, studies of alternative/improved coatings, studies of improved substrates (Si and float glass), design and assembly of new test modules where both LE and KB test modules were based on Multi Foil Technology (glass and Si substrates < 1mm) finished by tests in visible light and X-rays.